O processamento da anáfora conceitual por aprendizes de língua inglesa - Farias, Sheila Costa de (2015)
Studies on anaphoric processing include both the scope of the sentence and the scope of the discourse, therefore allowing for analyses that take into account not only strictly syntactic questions, but also phenomena at the interface between syntax, semantics and pragmatics. Here it was focused on this last point once it were observed relations between sentences specially dealing with the processing of conceptual anaphor when there is a collective noun as antecedent. In order to verify this phenomenon it were carried out three experimental studies with native Brazilian Portuguese language speakers; with native English language speakers at intermediate and advanced levels; and with learnerns of English language by using the self-paced reading technique. It was intended to observe what kind of retrieval takes longer to process: one in which the number and/or gender features of the antecedent and the pronoun are compatible (grammatical anaphor), or one in which the features are not compatible and it is necessary to access the semantic-pragmatic information (conceptual anaphor). Results allow us to conclude, on the one hand, that the grammatical anaphor is faster than the conceptual one, which shows the morphological level of the operation. On the other hand, the semantic-pragmatic information is accessed but it is in a later moment.